The The Chittagonian Coinage of Arakan’s Royal Sons - Hauret, Philip (Advances in Social Sciences Research Journal, 2022)
A researcher approaching the multi-lingual coins of the former Kingdom of Arakan (circa 1430-1784) must overcome many challenges. Difficult to read specimens, incorrect translations, poor scholarship and at times deficient photography within the existing treatments, when one can find them, are some of the obstacles encountered. Despite all the recent attention the Rohingya controversy has brought to these coins, studying them can still be productive of new information about Arakan. The objectives of this article are relatively modest, nonetheless. It will focus on a particular series of multi-lingual coins issued by a number of Arakanese-appointed governors of the Chittagong region, located in present-day Bangladesh, beginning in the 1570’s and ending circa 1612, with the aim of correcting some mistranslations and errors in descriptions as well as uncovering additional information about these governors, particularly those who were sons of Arakanese kings. It will also assess the effectiveness of the numismatic evidence in approximating the succession of these governors during the subject period. We will be assisted in this endeavor by the sale at auction of a major collection of Chittagonian coins in 2011 by Stephen Album Rare Coins (SARC) of Santa Rosa, California, a numismatic dealer specializing in Asian coinage. This unmatched assemblage of over 75 specimens offers students of Arakanese numismatics an unprecedented opportunity to study these coins, as today’s on-line auctions provide quality digital photography unavailable in the past.